2011
DOI: 10.1007/s10753-011-9373-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of Resting and Activated Monocyte-Derived Dendritic Cells Grown from Peripheral Blood of Patients with Ankylosing Spondylitis

Abstract: Decreased levels of class II major histocompatibility complex (MHC) expression and impaired formation of immunological synapse by dendritic cells (DCs) of HLA-B27 transgenic rats have been recently demonstrated. The resulting dysfunction of DCs may be implicated in the pathogenesis of the HLA-B27-related disease in transgenic animals. The phenotype of DCs in patients with ankylosing spondylitis (AS) has not been evaluated. Monocyte-derived DCs (MDDCs) were grown from patients with active AS and age-matched hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Despite this, evidence for IL-17–secreting T cells in inflamed, extra-articular tissues is limited [ 26–28 ]. Furthermore, examination of the critical myeloid populations has only been performed indirectly, using in vitro -generated mo-DCs [ 15 , 16 ]. These cultures do not recapitulate the diverse populations found in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, evidence for IL-17–secreting T cells in inflamed, extra-articular tissues is limited [ 26–28 ]. Furthermore, examination of the critical myeloid populations has only been performed indirectly, using in vitro -generated mo-DCs [ 15 , 16 ]. These cultures do not recapitulate the diverse populations found in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Most have heretofore focused on cells generated from monocytes following ex vivo culture with GM-CSF and IL-4 (mo-DCs) [ 14 ]. These express reduced surface MHC II expression compared with cells from healthy individuals, but no alteration in production of IL-23 or other cytokines [ 15 , 16 ]. On the other hand, in vitro studies do suggest that ER stress of DCs could lead to excessive IL-23 production [ 17 ], and as such they are intriguing candidate cells in initiating this effector pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive immune cells include helper T, Treg, CD8 + T, and B cells ( Rezaiemanesh, et al, 2018 ). Much evidence has demonstrated that certain phenotypes of resting and activated macrophages expressing scavenger receptor, CD163, can link between immune alterations of the gut and synovial inflammation in AS ( Baeten et al, 2002 ; Slobodin et al, 2012 ; Talpin et al, 2014 ; Wright et al, 2016 ; Rezaiemanesh et al, 2017 ). The abnormal polarization of macrophages induced by IL-4 was found in AS patients ( Lin et al, 2015 ).…”
Section: Immune Dysfunctions In Patients With Asmentioning
confidence: 99%
“…The level of circulating CD141+ dendritic cells (DCs) show a positive correlation with BASDAI in AS patients (53). Moreover, lower levels of MHC class II expression in DCs of AS patients (54) and animal model (55) implies that distortions in antigen presentation might very well be a key factor in disease pathogenesis.…”
Section: Arthritogenic Peptide/molecular Mimicry Hypothesismentioning
confidence: 99%